2004
DOI: 10.1111/j.1600-0897.2004.00189.x
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Toll‐like Receptors in Human Endometrial Epithelial Cells and Cell Lines

Abstract: RESULTS-TLR1-6 and 9 mRNA species were detected in both whole endometrium and separated endometrial epithelial cells. Ishikawa cells expressed TLR2 and TLR5, while RL95-2 cells expressed TLR3, 5, and 9. Response of RL95-2, Ishikawa, and U-937 cells to TLR2-5 ligands was consistent with RT-PCR findings except response to flagellin by Ishikawa cells.CONCLUSION-These studies provide the first evidence of TLR expression in the endometrium of any species and suggest the usefulness of endometrial cell lines to study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
84
1

Year Published

2004
2004
2018
2018

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 89 publications
(91 citation statements)
references
References 31 publications
(35 reference statements)
6
84
1
Order By: Relevance
“…Fichorova et al [21] demonstrated cervicovaginal epithelial cell line expression of TLR3. Our group established that endometrial epithelial tissues and cell lines express TLR3 as well as other TLRs [22]. Schaefer et al [23] independently confirmed this observation.…”
Section: Introductionsupporting
confidence: 69%
“…Fichorova et al [21] demonstrated cervicovaginal epithelial cell line expression of TLR3. Our group established that endometrial epithelial tissues and cell lines express TLR3 as well as other TLRs [22]. Schaefer et al [23] independently confirmed this observation.…”
Section: Introductionsupporting
confidence: 69%
“…In order to understand the expression patterns of the 20q defensin genes in female reproductive tissues, endometrial samples were obtained under a protocol approved by the UNC School of Medicine IRB from Dr Bruce Lessey (Greenville Hospital, Greenville, SC, USA) as described. 42 In all, 2 mg of total RNA was reverse transcribed using 50 U Stratascriptt (Stratagene, La Jolla, CA, USA) according to the supplier's instructions with 0.5 mg of oligodT (Invitrogen). Gene-specific intron spanning primer sequences for b-defensin DEFB118-DEFB123 and peptidyl isomerase (PPIA) were as follows:…”
Section: Methodsmentioning
confidence: 99%
“…The increase in expression of TLR2, TLR7, TLR8, and TLR9 in the endometrium during early pregnancy probably results from both progesterone-dependent recruitment of immune cells enriched in these particular TLRs (Segerson et al 1991, Plaks et al 2008, Gomez-Lopez et al 2010, Mansouri-Attia et al 2012 and changes in uterine gene expression required for pregnancy (Young et al 2004, Jorgenson et al 2005, Aflatoonian et al 2007, Hirata et al 2007, Turner et al 2012. In view of the significant increase in steady-state levels of both TLR7 and TLR8 mRNAs in uteri of early pregnant ewes, we determined cell-specific expression of TLR7 and TLR8 proteins to be particularly abundant in uterine LE and sGE and expressed in a temporal and cell-specific manner that differed due to reproductive TLR and establishment of pregnancy in sheep status, which supports results obtained from previous studies (Jorgenson et al 2005, Aflatoonian et al 2007, Hirata et al 2007.…”
Section: Discussionmentioning
confidence: 99%
“…The finding of TLRs in non-typical immune cells such as the epithelia (Young et al 2004, Turner et al 2012 has implicated these receptors in many physiological events besides pathogen recognition (Li et al 2010). Available evidence indicates potential involvement of TLRs in mammalian reproduction, which requires an appropriate inflammatory balance among steroid hormones, cytokines, and prostaglandins to assure cyclical uterine remodeling for establishment and maintenance of pregnancy (King & Critchley 2010, Ott & Gifford 2010, Dorniak et al 2011.…”
Section: Introductionmentioning
confidence: 99%